The Implementation of Multicultural Values on Vocational High School Students (A Research at Bagimu Negeriku Vocational High School Semarang) - Ardinastiti, Noviar; Masrukhi, Masrukhi; Suhandini, Purwadi (Universitas Negeri Semarang, 2019)
Bagimu Negeriku Vocational High School covers students from diverse cultural, religious, racial and ethnic backgrounds. This security requires the school to instill multicultural values in order to create a harmonious environment. The study aims to analyze the implementation of multicultural values applied by the school. This study was conducted qualitatively with a phenomenology approach. The research data sources were students, social studies teachers, student representatives, and school principals. The technique of data collecting were interviews, observations, and document studies which were tested for their validity through the source manipulation technique. The results of the study indicate that the implementation of multicultural values includes the value of justice; the school applies all students fairly, for example, the school does not distinguish students based on good deeds, both men and women have the same rights. The value of diversity; the school divides the composition of the class with a variety of students both from different tribes, different religions, and different areas of origin so that each class is a heterogeneous class. The value of freedom; it is embodied in some activities including the selection of extracurricular activities, and the value of solidarity; the school upholds the principle of